Producción de carbón activado a partir de cuesco de palma de aceite para la remoción de paraquat en solución acuosa (2019)
This research aims to contribute to the knowledge of product diversification and thermal treatments in the transformation of materials, seeking to generate alternatives to add value to agroindustrial waste. The production of activated carbon from oil palm kernel is studied. The activated carbon produced is evaluated by its capacity to adsorb the paraquat herbicide in aqueous solution. The thesis document is divided into three parts: First, a description of the raw material used is made, taking into account the information on the residual biomass generated in the country, its characteristics and the studies carried out by other researchers. The characteristics of activated carbon, the history of use of this material, the processes of obtaining and its applications are studied, with emphasis on liquid phase adsorption. Completing this section of context, the use of pesticide chemicals in national crops is reviewed, as well as methods to protect crops or eradicate plantations, the participation of paraquat, the risk of contamination of nearby watercourses and existing regulations. The second part presents the preparation, assembly and production of activated carbon in a fixed bed furnace, using water vapor as a reaction agent. It includes the definition of parameters and the design of the experimental plan to obtain activated carbon at temperatures of 750, 800, 850 and 900 ° C with different degrees of conversion from 22 % to 64 %. The objective of the different treatments is to evaluate the effect of the variation of parameters in the activation process and create porous structures with diverse surface characteristics to identify the properties of activated carbon that contribute to the adsorption of contaminant molecules. In order to determine the appropriate parameters for activation, characterization tests are carried out in the following part. This final phase contains the results of the characterization tests performed on samples of oil palm kernel shells, carbonized kernel shells and activated carbon from kernel shells. The comparison of results with samples of commercial activated carbon is made. Here the characteristics of the obtained surfaces, physical properties of the samples and results of adsorption tests are described. The surface area values of the activated carbon produced are between 750 and 1200 m2 / g approximately. Activated carbon with a higher degree of activation has the highest paraquat adsorption value per unit mass equal to 90 mg / g. With the results we found the parameters of the treatment that generated the activated carbon with the highest performance in the adsorption. From this the conclusions are established.